Valorization of Oil Palm Frond as a renewable carbon source for microbial bioflocculant production: a green approach to agricultural waste management - Agustin, Yuana Elly; Ma, Malvin; He, Ning; Yeap, Swee Keong; Hui, Yew Woh; Ding, Gongtao; Abdul Manaf, Shareena Fairuz; Jamali, Nur Syakina; Silvamany, Hemavathi; Tan, Jian Ping (Springer Science and Business Media B.V., 2026)
Despite Oil Palm Fronds (OPFs) being the most abundant harvestable lignocellulosic biomass residue in Asian region, they remain underutilized, contributing to greenhouse gas emissions when left to decompose in plantations. This study explores the feasibility of using enzymatically hydrolyzed OPF hydrolysate as a carbon source to partially substitute glucose in bioflocculant production. We hypothesize that OPF hydrolysate can serve as a viable carbon source for bioflocculant synthesis while minimizing environmental effect. Enzymatic hydrolysis with Cellic® Ctec3 without acid or alkaline pretreatment resulted in the highest reducing sugar yield (13.3 ± 0.2 g/L). A 40:60 OPF hydrolysate-to-glucose ratio yielded optimum bioflocculant yield (8.3 g/L) without compromising flocculating activity (87%). The produced bioflocculant remained stable across pH 3–7 and 4–30 °C. A preliminary life cycle assessment estimated a 58.8% carbon footprint reduction can be achieved compared to the glucose-only benchmark. These findings demonstrate OPF’s potential as a sustainable feedstock for bioflocculant production.